UPAYA MENINGKATKAN KEMAMPUAN BERBICARA MELALUI METODE STORYTELLING DENGAN MEDIA ROTATUN PADA ANAK USIA 4-5 TAHUN DI PAUD HARAPAN KECAMATAN SAIL - Susilawati, Endang; Zulkifli N, Zulkifli N; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This study aims to determine how much influence on the ability to speak Storytelling method children in children aged 4-5 years in early childhood Hope District of Sail. This study consists of two variables: Methods Storyelling and Speech. The hypothesis of this study are as follows: Suspected using storytelling method can improve speaking skills of children aged 4-5 years in early childhood Hope Village sukamulia sail districts pekanbaru city. Method of Action Research (PTK). Data collection techniques in this study using observation. The data analysis technique used is a model of the flow of data reduction. Results of this study showed significant improvement. Increase in the average ability of speaking children of pre-cycle to the first cycle was 26% in the category Start Evolving (MB), from the first cycle to the second cycle increased ability to speak the child reaches 46%, in the category Start Evolving (MB) and of Pre cycle to the second cycle of the total increase in the average number reached 85% which is included in the category Emerging Very Good (BSB).Keywords: Storyelling method, Speech